Green House Effect Cause And Effect: A Analytical Study - Dr. Yogendra Singh (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2018)
The 21st century is remarkable from many points of view, in this century man has achieved many achievements from social, economic, industrial, and technical points of view. Due to consumerist attitudes and competition, the resources provided by nature are being rapidly consumed. Due to this, the available resources are not only depleting rapidly but their quality is also getting affected. As a result of excessive exploitation of resources, the Earth's atmosphere has reached a critical point, which is a matter of worldwide concern and can also lead to the destruction of the Earth. The United Nations Environment Program (UNEP) presented its report in 1990, to which more than 200 scientists from 26 countries contributed. In this IPCC report, the greenhouse effect was considered the biggest culprit for climate change and environmental degradation. However, due to the proper proportion of greenhouse gases, the earth remains habitable for all living beings. If this had not happened, the average temperature of the Earth would have been about 350 Celsius less than today and the planet Earth would have been unfit for the life of the fauna and flora like other planets.